1992
DOI: 10.1007/bf01624152
|View full text |Cite
|
Sign up to set email alerts
|

Risk of osteoporosis in men with chronic bronchitis

Abstract: Theoretically, patients with chronic bronchitis are at risk for osteoporosis. Bone metabolism was assessed in 44 male chronic bronchitics treated with oral prednisolone (C+; n = 19) or with bronchodilatory drugs alone (C-; n = 25). In both groups, serum osteocalcin was lower (p less than 0.001) than in age- and sex-matched controls (mean (ng/ml) C+ 1.0, C- 1.9, controls 4.2), while testosterone was at the lower limit of the reference range. Low trabecular bone mineral density (BMD) was noted in the C- group (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 34 publications
0
27
0
1
Order By: Relevance
“…Primers and TaqMan probes were designed using the Primer Express 1.0 (Applied Biosystems) software to amplify Ͻ 150 base pairs. Probes were labeled at the 5Ј end with the reporter dye molecule 6-carboxy-fluorescein (FAM) (22) and at the 3Ј end with the quencher dye molecule 6-carboxytetramethyl-rhodamine (TAMRA). The target gene and the housekeeping gene (glyceraldehyde-3-phosphate dehydrogenase [GAPDH]) were simultaneously tested in duplicate or triplicate.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Primers and TaqMan probes were designed using the Primer Express 1.0 (Applied Biosystems) software to amplify Ͻ 150 base pairs. Probes were labeled at the 5Ј end with the reporter dye molecule 6-carboxy-fluorescein (FAM) (22) and at the 3Ј end with the quencher dye molecule 6-carboxytetramethyl-rhodamine (TAMRA). The target gene and the housekeeping gene (glyceraldehyde-3-phosphate dehydrogenase [GAPDH]) were simultaneously tested in duplicate or triplicate.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Cross-sectional studies have revealed that bone mass is reduced in patients with COPD (3,4). Bone mass loss is caused by malnutrition, immobility, and hormonal imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…This programme included spinal radiography and, in some centres, measurements of BMD by dual-energy X-ray absorptiometry. Since both COPD and smoking are themselves risk factors for osteoporosis [1,14], EUROSCOP provided a valuable opportunity to evaluate the impact of long-term inhaled corticosteroid therapy on bone density and metabolism in a population at risk of osteoporosis. The radiographical and BMD data from patients who completed the study are presented in this paper.…”
mentioning
confidence: 99%